Early indoor aeroallergen exposure is not associated with development of sensitization or allergic rhinitis in high‐risk children. Issue 5 (2nd March 2016) - Schoos, A.‐M. M.; Chawes, B. L.; Jelding‐Dannemand, E.; Elfman, L. B.; Bisgaard, H.
Abstract: Rationale: Allergen exposure is associated with the development of allergic sensitization in childhood as reflected by global variations in sensitization patterns. However, there is little evidence to support a direct association. Objectives: To investigate the association between perinatal aeroallergen exposure and sensitization and rhinitis to such allergens later in childhood. Methods: Allergic sensitization to cat, dog, and house dust mites was diagnosed longitudinally using skin prick tests and specific IgE measurements at ½, 1½, 4, 6, and 13 years in 399 children from the Copenhagen Prospective Study on Asthma in Childhood2000 birth cohort. Rhinitis was diagnosed at 7 and 13 years. Allergen exposure was defined as dog or cat in the home during the 3rd trimester of pregnancy or the first year of life and as allergen levels of dog, cat, and house dust mite in bed dust samples at 1 year. Associations between exposure and outcomes were analyzed by logistic regression and stratified for eczema status and test method (skin prick test and specific IgE). Results: We found no association between dog or cat exposure in perinatal life and sensitization or rhinitis during childhood. Similarly, there was no association between levels of allergens in bed dust samples and sensitization or rhinitis during childhood. Conclusion: Perinatal indoor aeroallergen exposure does not seem to affect development of allergic sensitization or rhinitis during childhood questioning the relevance of allergen avoidance as a preventive measure. Other factors such as timing of allergen exposure or other environmental adjuvants may contribute in a more complex pathway to sensitization.